1995
DOI: 10.1084/jem.181.3.1047
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic T lymphocyte response to multiple hepatitis B virus polymerase epitopes during and after acute viral hepatitis.

Abstract: Cytotoxic T lymphocytes (CTL) are thought to contribute to viral clearance and liver cell injury during hepatitis B virus (HBV) infection. Using a strategy involving the in vitro stimulation of peripheral blood mononuclear cells (PBMC) with HBV-derived synthetic peptides containing HLA-A2.1, -A31, and -Aw68 binding motifs, we have previously described CTL responses to several epitopes within the HBV nucleocapsid and envelope antigens in patients with acute hepatitis. In this study we define six HLA-A2-restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
354
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(367 citation statements)
references
References 30 publications
12
354
0
Order By: Relevance
“…It is conceivable that these two findings may represent the opposite sides of the same dynamic equilibrium, in which the persisting virus is kept under control through continuous elimination of infected cells by virus-specific immune responses. Vigorous HBV-specific cytotoxic T-lymphocyte reactivity demonstrated in the peripheral blood of patients years after recovery from acute hepatitis B, 3,4 suggesting sustained re-exposure of the T cells to virus antigens, could be consistent with the above interpretation. HCC ultimately developed in 2 of the 9 (22%) woodchucks within 35.5 and 56 months after apparent complete resolution of WHV infection.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is conceivable that these two findings may represent the opposite sides of the same dynamic equilibrium, in which the persisting virus is kept under control through continuous elimination of infected cells by virus-specific immune responses. Vigorous HBV-specific cytotoxic T-lymphocyte reactivity demonstrated in the peripheral blood of patients years after recovery from acute hepatitis B, 3,4 suggesting sustained re-exposure of the T cells to virus antigens, could be consistent with the above interpretation. HCC ultimately developed in 2 of the 9 (22%) woodchucks within 35.5 and 56 months after apparent complete resolution of WHV infection.…”
Section: Discussionsupporting
confidence: 72%
“…[1][2][3][4][5] In these convalescent patients, HBV DNA have been detected both in serum and in circulating lymphomononuclear cells, often despite the presence of neutralizing antibodies to virus envelope (hepatitis B surface antigen) 2,3,5 and a vigorous polyclonal HBV-specific cytotoxic T-cell response. 3,4,6 In addition, traces of hepatitis B surface antigen and HBV-DNA-reactive particles with physicochemical properties of intact virions have been detected in the circulation of some of the recovered individuals. 2 These findings imply that HBV eradication does not coincide with the rise of antivirusspecific humoral and cellular immune responses and with clinical resolution of acute hepatitis.…”
mentioning
confidence: 99%
“…In other persistent viral infections such as lymphocytic choriomeningitis virus (41)(42)(43), hepatitis B virus (44,45), and HIV (46,47), it has been demonstrated that virus-specific, CD8 ϩ T cells undergo repeated activation that ultimately results in activation-induced cell death (48). During a chronic EBV infection, it is possible that virus-specific CTL frequently encounter their cognate Ags on the surface of EBV-transformed B cells and that the continuous exposure of these CTL to EBV epitopes eventually results in activation-induced cell death and their disappearance from the memory T cell population.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 As with HCV infection, the host immune response to HBV infection determines viral persistence, 16,17 which has been associated with polymorphisms in the human leukocyte antigen complex and other immune response genes. [18][19][20][21][22][23][24] Although there are likely important differences in the mechanisms of HBV persistence, there is also evidence that NK T (NKT) cells play an important role.…”
Section: Introductionmentioning
confidence: 99%